Raman-Infrared spectroscopy, thermal behaviour, dielectric, and UV-fluorescence studies of [C6H5NH3]3BiCl6·3H2O. (December 2021) - El-Adel, L.; Ouasri, A.; Rhandour, A.; Hajji, L.
Abstract: This paper aims to study spectroscopy, thermal, dielectric, and photoluminescence properties of [C6 H5 NH3 ]3 BiCl6 ·3H2 O, which was investigated elswehere [Orthorhombic system P 21 21 21 (Z = 4)]. Indeed, the simulated crystal morphology made with the Bravais, Friedel, Donnay and Harker (BFDH) method is very close to the experimental observation taken under scanning electronic microscopy (SEM). The Raman spectrum (50-3400 cm −1 ) at ambient temperature is interpreted considering the D2 factor group, in which the BiCl6 3− anions occupied C1 (2) symmetry sites. The Infrared spectra, recorded at ambient temperature and 140 °C, are studied to confirmed the removing of water molecules above the compound dehydratation. The dehydratation-decomposition behaviour of [C6 H5 NH3 ]3 BiCl6 ·3H2 O is studied by the differential scanning calorimetry (DSC) analyses (5 °C.min −1 ), which shows that the title compound is decomposed immediately above the dehydration process at 130 °C. The thermal behaviour study is supported by the dielectric analyses, performed in the (20–150 °C) temperature domain and (50 kHz - 1 MHz) frequencies. So, three dielectric permittivity (εr ) anomalies (T1  = 85 °C, T2  = 115 °C, T3  = 126 °C) are shown in agreement with the DSC analyses; the (εr ) dispersion across the dehydratation process implied the appearance of electric conductivity. The variation of the dielectric dissipation tgδ versus temperature at (50 kHz - 1 MHz) is studied. The fluorescence excitation and emission spectra show that the compound undergoes indigo-blue photoluminescence (PL) with two emission signals at 414 nm (2.991 eV) and 424 nm (2.921 eV), when it was excited at 400 nm (3.096 eV) ( λ max excitation). This suggests potential applications for this compound as UV detection and optical materials. Highlights: The [C6 H5 NH3 ]3 BiCl6 ·3H2 O crystal morphology is simulated according to the scanning electronic microscopy. The Raman spectrum of this compound is studied based on theoretical group analyses. The dehydratation-decomposition of the title compound is studied by IR spectra, DSC and dielectric analyses. Optical analyses showed indigo-blue photoluminescence (PL) for [C6 H5 NH3 ]3 BiCl6 ·3H2 O.